Evaluación comparativa bromatológica y contenido de actividad oxidativa Portulaca oleracea verdolaga cruda y cocida, Iquitos - 2021 - Rodriguez Rivas, Claudia Ermilia (2022)
The present investigation was carried out in the facilities of the pilot plant of the Faculty of Food Industries and CIRNA, its objective was to carry out comparative bromatological analysis and determine antioxidants of the raw material Portulaca Oleracea , both as fresh dry and cooked dry state, for the first In the state, the raw material was harvested from the facilities of the Experimental Center for Medicinal Plants of the Faculty of Agronomy, located in Zungaro Cocha, having Bautista as location. This area has the following coordinates: X: 680869. 2341837081, Y: 9576394. 801042935, Zone: 18, hemisphere: South, having a harvest time of 75 days, Then it was transferred to the facilities of the pilot plant of the Faculty of Food Industries, where it was weighed, classified and dried at room temperatures (32 o C) under shade, at this stage it included leaves and branches of purslane, after 4 days drying was ground and stored in bags of 100 grams. Then it was done in a 100-gram bag, it was cooked at 100 o C, for 10 minutes, and then dried at room temperature for a time of 6 days. Once the dry samples were obtained, the physical chemical analyzes (macro nutrients) were carried out, reporting the following results: humidity: 93.40 g, ash: 1.30 g, fat: 0.25 g, proteins: 1.89 g, carbohydrates: 3.16 g , calories: 22.45 Kcal, titratable acidity (H 2 SO4 ): 0.12%, pH (25 o C): 5.98, dry matter: 6.60 g, as for dry cooked purslane: moisture: 13.39 g, ash: 26.28 g, fat: 2.93 g, proteins: 19.12 g, carbohydrates : 38.28 g, calories: 255.97 Kcal, titratable acidity: ( H 2 SO 4 ): 0.29%, Ph (25 o C): 5.95, dry matter: 86.61 g, calcium: 162.24 mg, phosphorus: 11.80 g, phosphorus: iron : 1.10 mg, potassium: 328.00 mg, then in the CIRNA laboratory, the standard curves were made with DPPH, and the readings were diluted with different solvents such as: petroleum diethyl ether, chloroform, ethanol, benzene, ethanol mixtures plus distilled water, not being able to make a good separation of the extracts, but a good extraction with double distilled water, and from there it was started to make the oxidative capacity and total phenols of 0.392 and 0.254 ?mlTE/ml. m.s. readings of the two samples of purslane.